DIVERGING SOCIAL ORDERS OF EUROPE AND RUSSIA AFTER THE MIDDLE AGES, AND LONG-TERM POLITICAL CONSEQUENCES - N. S. Rozov (Сравнительная политика)
Medieval Europe before the Reformation and Moscow Russia before the Troubles are viewed in an ideally-typical manner as carriers of basic social and mental unities: faith and church organization, sacred empire as the Rome’s usccessor, basic social relations. As a result of the Reformation and the religious wars each of the European unities was destroyed, but parts of the former Pax Christiana continued to closely interact and compete with each other, to fight for leadership, that led to intensive modernization of the leading Western European powers with known global consequences. Moscow State after the Time of Trouble restored its unity in all three aspects. The features of the state and society here were significantly transformed as a result of the Schism, the formation of the Russian empire, administrative reforms of the 18–19 centuries, but the basic properties of etatism, centralism, priority of service, and power instrumentalization of the moral and religious sphere remained. The Russian social-political cycles have the phases: successful mobilization, stagnation, crisis, attempts of liberalization, authoritarian scrollback. The cyclical dynamics is explained by the interrelation of the following factors: 1) the primacy of military-compulsory (“colonial”) administration as a means of retaining and managing vast territories; 2) the state priorities of military power, size of the territory, and the volume of export products; 3) the order of military service as a basic model for political and social institutions; the corresponding weakness of autonomous capital and business activity; 4) the mental, cultural and property gap (lack of vertical solidarity) between the elites and the bulk of the population. 5) the monopoly of state religion (or forced atheism). Thus, unity of political power, religious and ideological monopoly can lead a country to military triumphs and even geopolitical success for decades but in the longue duree this unity generates vulnerability.